Sounion revisited : the santuaries of Poseidon and Athena at Sounion in Attica - Theodoropoulou-Polychroniadis, Zetta (Archaeopress archaeology., 2015)
This work is the first to be published from a wider research project, still in progress, about the sanctuaries of Poseidon and Athena on the promontory of Sounion (southeast Attica). The aim of this volume is to present, for the first time, a comprehensive examination and interpretation of a wide selection of unpublished small finds.